2016
DOI: 10.1097/md.0000000000005056
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided continuous femoral nerve block vs continuous fascia iliaca compartment block for hip replacement in the elderly

Abstract: Background:Continuous femoral nerve block and fascia iliaca compartment block are 2 traditional anesthesia methods in orthopedic surgeries, but it is controversial which method is better. The objective of this study was to compare the practicality, efficacy, and complications of the 2 modalities in hip replacement surgery in the elderly and to assess the utility of a novel cannula-over-needle set.Methods:In this prospective, randomized controlled clinical investigation, 60 elderly patients undergoing hip repla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 17 publications
1
34
0
1
Order By: Relevance
“…The FICB has been used in several types of surgeries. Yu et al compared a continuous femoral nerve block and a continuous fascia iliaca compartment block in THA surgery for elder patients and found that the continuous fascia iliaca compartment block has a better effect on pain condition [23]. Williams et al revealed that standard analgesia combined with FICB significantly reduced the VAS scores of patients with femoral neck fractures after surgery [24].…”
Section: Discussionmentioning
confidence: 99%
“…The FICB has been used in several types of surgeries. Yu et al compared a continuous femoral nerve block and a continuous fascia iliaca compartment block in THA surgery for elder patients and found that the continuous fascia iliaca compartment block has a better effect on pain condition [23]. Williams et al revealed that standard analgesia combined with FICB significantly reduced the VAS scores of patients with femoral neck fractures after surgery [24].…”
Section: Discussionmentioning
confidence: 99%
“…17 Yu et al, compared continuous FICB and continuous FNB for postoperative pain relief in elderly patients who underwent hip replacement under general anaesthesia. 18 Postoperative VAS scores were comparable in both the groups.…”
Section: Discussionmentioning
confidence: 80%
“…Another study suggested that both ultrasound-guided continuous femoral nerve block and fascia iliaca compartment block with a novel cannula-over-needle provide effective anesthesia and postoperative analgesia for elderly patients with hip replacement (35). It has been reported that 3-in-1 femoral nerve block is also effective in hip fracture analgesia (20,36).…”
Section: Discussionmentioning
confidence: 99%